2014
DOI: 10.1117/1.jmi.1.3.031009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of image-based phenotypes of mammographic density and parenchymal patterns in distinguishing betweenBRCA1/2cases, unilateral cancer cases, and controls

Abstract: Abstract. We statistically compare the contributions of parenchymal phenotypes to mammographic density in distinguishing between high-risk cases and low-risk controls. The age-matched evaluation included computerized mammographic assessment of breast percent density (PD) and parenchymal patterns (phenotypes of coarseness and contrast) from radiographic texture analysis (RTA) of the full-field digital mammograms from 456 cases: 53 women with BRCA1/2 gene mutations, 75 with unilateral cancer, and 328 at low risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 34 publications
1
36
0
2
Order By: Relevance
“…However, Li et al were among the very first to apply texture analysis to discriminate between high-risk BRCA-mutated and low-risk wild-type patients [118]. AI methods were subsequently leveraged to improve the performance of these radiogenomic predictive models-first with Bayesian artificial neural networks, a framework for different machine learning algorithms [119,120], and then with convoluted neural networks (AUC = 0.86) [121].…”
Section: Breast and Ovariesmentioning
confidence: 99%
“…However, Li et al were among the very first to apply texture analysis to discriminate between high-risk BRCA-mutated and low-risk wild-type patients [118]. AI methods were subsequently leveraged to improve the performance of these radiogenomic predictive models-first with Bayesian artificial neural networks, a framework for different machine learning algorithms [119,120], and then with convoluted neural networks (AUC = 0.86) [121].…”
Section: Breast and Ovariesmentioning
confidence: 99%
“…This set of quantitative features was evaluated because the constituent features have demonstrated utility in previous studies involving clinical classifications based on parenchyma regions in FFDM images. [6][7][8]25…”
Section: B Radiomic Feature Calculationmentioning
confidence: 99%
“…Quantitative measures of parenchymal texture have been successfully applied to evaluate the risk of cancer in asymptomatic females . These studies use radiomic texture features including fractal dimension, power law spectral analysis, absolute gray level, gray‐level histogram analysis, neighborhood gray tone difference matrix (NGTDM), and gray‐level co‐occurrence matrix (GLCM) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 An abundance of evidence exists demonstrating a positive correlation between mammographic percent density and breast cancer risk. [4][5][6][7][8][9][10] In addition to density, various studies have indicated a relationship between parenchymal texture patterns and risk of cancer development [11][12][13][14][15][16][17][18][19][20][21] or specific cancer risk factors such as BRCA1/BRCA2 gene mutation. 11,21 Percent density obtained from mammographic images refers to the ratio of the area of dense tissue present in a mammogram to the total area of the breast.…”
Section: Introductionmentioning
confidence: 99%